Recent Publications (Quarterly Journal of Economics, 1946)
Recent Publications Get access The Quarterly Journal of Economics, Volume 61, Issue 1, November 1946, Pages 169–172, https://doi.org/10.1093/qje/61.1.169 Published: 01 November 1946